The factors contributing to tesl students' reluctance to speak in english / Syazwani Che Noh - Che Noh, Syazwani (2014)
This study seeks the factors contributing to TESL students' reluctance to speak in English. The factors have been categorized into three main categories which are Social Factors, External Factors and Internal Factors. TESL students believed that their reluctance to speak in English is mainly influenced by the External Factors which comprises of the environment and the social setting the TESL students are living in. Other than that, this study also seeks if there is any correlation between the three main categories of factors listed in this study. It was found out that there are three correlations exist between the main categories of factors. The significant negative correlation was shown by the internal factors and social factors. The external factors and internal factors as well as the social factors and external factors both signify insignificant positive correlation.